2007
DOI: 10.1186/1472-6963-7-202
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a method for identifying nursing home admissions using administrative claims

Abstract: Background: Currently there is no standard algorithm to identify whether a subject is residing in a nursing home from administrative claims. Our objective was to develop and validate an algorithm that identifies nursing home admissions at the resident-month level using the MarketScan Medicare Supplemental and Coordination of Benefit (COB) database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Population-based administrative databases have been successfully used for case-identification of medical conditions in the general population [15][16][17][18][19][20][21][22][23]. Using administrative databases is relatively inexpensive, minimizes usual biases associated with survey studies (recall bias, nonresponse, and subject attrition), and increases external validity compared with cohort studies [15,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based administrative databases have been successfully used for case-identification of medical conditions in the general population [15][16][17][18][19][20][21][22][23]. Using administrative databases is relatively inexpensive, minimizes usual biases associated with survey studies (recall bias, nonresponse, and subject attrition), and increases external validity compared with cohort studies [15,21].…”
Section: Introductionmentioning
confidence: 99%
“…Physician-billing claims databases (PCDs) are a valid source of information for outcome assessment [15][16][17][18][19][20][21][22][23]. Since fractures are typically acute and painful, they are easily recognized and promptly treated within the healthcare system [17] and consequently, should be identifiable from PCDs.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies identified nursing facility stays, they did not distinguish between short and long stays (Iwashyna 2003;Zuckerman et al 2007). Further, these studies were cross-sectional, with limited sample size or used claims based upon beneficiaries with supplemental insurance only.…”
Section: Discussionmentioning
confidence: 94%
“…Two studies have addressed the issue of detecting nursing facility use and nursing facility admissions in Medicare claims data (Iwashyna 2003;Zuckerman et al 2007). These studies did not differentiate between short-and long-term nursing facility care.…”
Section: Introductionmentioning
confidence: 99%
“…Zuckerman et al [16] described an algorithm to combine different types of provider claims to predict whether patients lived in a nursing home. Lix et al [17] combined information from hospital, physician, and pharmacy administrative data sets to predict the probability that patients had osteoporosis.…”
Section: Discussionmentioning
confidence: 99%